PENGGUNAAN WEBSITE PADANG.GO.ID UNTUK MEMENUHI LAYANAN INFORMASI PUBLIK BAGI MASYARAKAT DI KOTA PADANG - Aldri Frinaldi; Saskia Pratiwi Danda (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2023)
The backdrop of this study is the poor user interest in utilizing the padang.go.id website. The goal of this study is to evaluate how the Padang.go.id website is used to provide public information services for the residents of Padang City based on the effectiveness of the system, the reliability of the information, and the usability of the website, as well as any barriers to its use and the efforts made by the Padang City Diskominfo. Qualitative research is conducted using descriptive techniques and an inductive methodology. data gathered by using observational techniques, conducting interviews, and keeping records. Data reduction, data display, and conclusion-making were all used in data analysis. According to the study's findings, the Padang.go.id website has not been used effectively, the completeness and quality of the information are still ineffective owing to infrastructure, facilities, and human resources, and the website is not used frequently because of a lack of socializing. Diskominfo is therefore anticipated to be able to create this digital platform to accomplish effective information distribution to the general public